Gram-scale production of forskolin in yeast through biosynthetic network elucidation and pathway optimization - Meiling Jiang; Hao Tang; Ying Ma; Zhenjiang Tian; Wenbo Xu; Xinqi Song; Lan Kang; Luqi Huang; Yating Hu (Bioresource Technology, 2026)

Multiscale characterization and velocity-related risk zoning of impact damage in mature broccoli under controlled single-impact simulation - Liming Qin; Meiling Yuan; Zheng Xu; Jiajun Wu; Jingbin Li (Postharvest Biology and Technology, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Remediation of Black and Odorous Water using a Slow-release Composite Agent Containing CaO2, Zeolite, and Polymeric Ferric Sulfate: Effects on Water Quality and Chlorella Growth - Jinhai Li; Defu Xu; Yafei Xun; Ying Zhuang; Meiling Guan; Alan Howard (Water, Air, & Soil Pollution, 2026)

Genome-wide characterization of terpene synthase genes in Ginkgo biloba and their regulatory role in terpene trilactones biosynthesis - Ang Xu; Chenglin Luo; Chunxia Chen; Yumeng Gao; Wenjing Qin; Qi Wang; Lisha Shi; Xiaoming Yang; Meiling Ming; Fuliang Cao; Fangfang Fu (Plant Science, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Effects of CaCl2 on the lipid properties of rapidly salted separated egg yolk and lipidomic analysis - Yaotong Liu; Meiling Xu; Yajie Chang; Shiwen Xu; Yujie Chi (Food Research International, 2026)

Seamless 1-km hourly land surface temperature estimation via multi-source data integration and automated machine learning - Yumin Li; Meiling Gao; Zhenhong Li; Penghai Wu; Bin Wang; Rongtang Xu; Guijun Yang (Urban Climate, 2026)

Removal of organochlorine from the oil phase by poly(BMA-co-SMA-co-DAP) acrylic resin: Adsorption selectivity, kinetics, thermodynamics, molecular simulation and DFT calculations - Pan Luo; Xi Deng; Yingchun Lu; Meiling Li; Guihong Lan; Haiyan Qiu; Bo Xu; Yinli Peng (Journal of Environmental Chemical Engineering, 2026)

Elevated CO2 synergizes with nanoplastics to intensify arsenic mobilization, biotransformation, and plant uptake in soil-spinach systems - Wei Li; Yabo Wang; Yuling Suo; Zishu Zheng; Qiao Xu; Meiling Xu; Fen Xu; Weiqin Yin; Shengsen Wang; Xiaozhi Wang (Environmental Pollution, 2026)

Design and Performance Evaluation of Amino Acid-Decorated UiO-66-NH2/Pebax Mixed Matrix Membranes for Efficient CO2 Separation - Xiaochun Jing; Wei Zhao; Pengzhi Bei; Hongjing Liu; Yan Dai; Xu Zhao; Chengpeng Zhang; Meiling Shi; Ying Zhang (Water, Air, & Soil Pollution, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

Deciphering the mechanisms of phosphorus concentration in regulating nitrogen removal and autoaggregation of Pseudomonas stutzeri - Hanbo Zhao; Jie Huang; Meiling Tong; Yanghua Ou; Zhixuan Yu; Xiaowei Xu; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2026)

Particulate organic carbon dominates early-stage soil carbon accumulation in restored mangroves across estuarine zones - Leiyu Wang; Dalong Jiang; Zuo Xu; Tao Nie; Meiling Hong (Journal of Environmental Management, 2026)

Valorization of saline byproducts: Development of composite films from waste salted egg white and plant extracts - Meiling Xu; Yajie Chang; Xuying Wang; Shiwen Xu; Yaotong Liu; Yanqu Ma (Food Research International, 2026)

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

Deep-sea bamboo corals: New Jasonisis species from Indian and Atlantic ridges and pan-oceanic genetic connectivity of Tridentisis candelabrum - Meiling Ge; Xinlong Li; Xin Tian; Ningxia Xu; Xuying Hu; Yu Xu; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Ecological distribution and functional characterization of polyethylene-degrading enzymes from diverse metagenomes - Ning Wang; Meiling Jin; Zixuan Zhu; Yuxin Wang; Xinyu Li; Jing Xu; Shijunyi Cheng; Yuanying Zhu; Ruiqi Wang; Tong Xu; Furong Yin; Xinyue Li; et al. (Science of The Total Environment, 2026)

Microbial-driven iron transformation and carbon stabilisation in flooded soils: roles of biochar and rock weathering - Qiao Xu; Gefeng Zhang; Feifan Zhang; Tharanga Bandara; Hongyan Guo; Meiling Xu; Caixian Tang (Plant and Soil, 2026)

Underwater Noise in Offshore Wind Farms: Monitoring Technologies, Acoustic Characteristics, and Long-Term Adaptive Management - Peibin Zhu; Zhenquan Hu; Haoting Li; Meiling Dai; Jiali Chen; Zhuanqiong Hu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The rapid global expansion of offshore wind energy (OWE) has established it as a critical component of the renewable energy transition; however, this development concurrently introduces significant underwater noise pollution into marine ecosystems. This paper provides a comprehensive review of the acoustic footprint of OWE across its entire lifecycle, rigorously distinguishing between the high-intensity, acute impulsive noise generated during pile-driving construction and the chronic, low-frequency continuous noise associated with decades-long turbine operation. We critically evaluate the engineering capabilities and limitations of current underwater acoustic monitoring architectures, including buoy-based real-time monitoring nodes, cabled high-bandwidth systems (e.g., cabled hydrophone arrays with DAQ/DSP and fiber-optic distributed acoustic sensing, DAS), and autonomous seabed archival recorders (PAM deployment). Furthermore, documented biological impacts are synthesized across diverse taxa, ranging from auditory masking and threshold shifts in marine mammals to the often-overlooked sensitivity of invertebrates and fish to particle motion—a key metric frequently missing from standard pressure-based assessments. Our analysis identifies a fundamental gap in current governance paradigms, which disproportionately prioritize the mitigation of short-term acute impacts while neglecting the cumulative ecological risks of long-term operational noise. This review synthesizes recent evidence on chronic operational noise and outlines a conceptual pathway from event-based compliance monitoring toward long-term, adaptive soundscape management. We propose the implementation of integrated, adaptive acoustic monitoring networks capable of quantifying cumulative noise exposure and informing real-time mitigation strategies. Such a paradigm shift is essential for optimizing mitigation technologies and ensuring the sustainable coexistence of marine renewable energy development and marine biodiversity.

Seasonal gut microbiota and functional dynamics in brittle star (Ophiothrix exigua) from the Yellow Sea, China - Md. Tariful Islam Fuad; Yue Dong; Zhong Li; Meiling Ge; S.M. Sharifuzzaman; Xiaoshou Liu; Xuelei Zhang; Qinzeng Xu (Marine Environmental Research, 2026)

Cationic polyacrylamide (CPAM) assisted leaching of rare earth ore containing clay minerals by inhibiting swelling and promoting permeation of ammonium sulfate solution - Meiling Jiang; Huifang Yang; Wenqian Cui; Yunbo Yang; Zhenyue Zhang; Zhengyan He; Zhigao Xu; Ming Wu; Jun Zhao; Ruan Chi (Hydrometallurgy, 2026)

Disentangling adaptive strategies of eukaryotic phytoplankton to environmental stressors in the sediment-laden Yellow River: A multi-method perspective from eDNA and morphology - Meiling Yi; Shuang Xu; Feilong Li; Bowen Gao; Yang Li (Environmental Research, 2026)

Long non-coding RNA profiling reveals lncRNA MslncLOX13S that promotes lipoxygenase gene expression and enhances the tolerance to selenium in Medicago sativa L. - Qingdong Wang; Mengli Xu; Meiling Xiang; Yarui Sheng; Huafeng Hu; Tianyu Zhang (Journal of Plant Physiology, 2025)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

Laser-engineered rattan evaporators for scalable and sustainable solar desalination - Haocheng Xu; Yingpeng Liu; Pei Qi Woon; Meiling Chen; Xinwu Xu; Bofan Li (Chemical Engineering Journal, 2025)

EDIL3 induced by GLIS2 suppresses the anti-tumor activity of CD8+ T cells and expedites epithelial-mesenchymal transition in thyroid cancer - Xu Qian; Bo Fu; Shuangfu Peng; Meiling Xue; Zhaohui Zhu; Dan Yao (Journal of Molecular Histology, 2025)

Grass-legume mixture optimizes soil new carbon sequestration by leveraging microbial necromass dynamics in a pear orchard - Qiao Xu; Yingdong Zhao; Meiling Xu; Jinlong Dong; Weiqin Yin; Jing Ma; Xiaozhi Wang (Agriculture, Ecosystems & Environment, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

Sequential temperature design in high-speed railway stations: A dynamic thermal strategy balancing thermal comfort and energy efficiency - Ye Yuan; Meiling Li; Junxi Gao; Gang Liu; Zongwu Xu; Ying Chen; Hanyuan Zhang (Building and Environment, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

The intergrowth of YTa7O19 in L-Ta2O5 with Er3+/Yb3+ enhancing pure green upconversion luminescence intensity by molten salt synthesis - Yuhan Fan; Yongze Cao; Zhihua Zhang; Hualong Tao; Meiling Li; Xizhen Zhang; Sai Xu; Baojiu Chen (Chemical Engineering Journal, 2025)

CBT-Cys click ligation coupled with pregnancy test strips for nucleic acid assay - Meiling Zhang; Jiahang Song; Huawen Zhang; Yang Li; Xu Hun (Analytica Chimica Acta, 2025)

Consumer preference of new energy vehicles and regional heterogeneity in China: the role of emotion and region - Yuanyuan Wang; Jin-Hua Xu; Meiling Chen (Environment, Development and Sustainability, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Environmental Impacts and Behaviors of Chromium in Pakchoi-Soil Systems Under Ambient and Elevated CO2 Levels - Yuning Wang; Yatu Huang; Ye Ding; Wentao Yang; Yabo Wang; Qiao Xu; Yao Yao; Xiaozhi Wang; Meiling Xu (Water, Air, & Soil Pollution, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Different responses of cyanobacterial communities to climate change and anthropogenic activities revealed by the 500-year sedimentary record of Lake Daihai - Jing Wang; Hai Xu; Jianghu Lan; Kang’en Zhou; Yunping Song; Jin Zhang; Meiling Yang; Baoli Wang (Anthropocene, 2025)

Oxidation temperature-dependency of relative dielectric constant and reflective characteristics of lignite and bituminous coal in the presence of very high frequency to ultra-high frequency bands - Qi Liao; Meiling Zhu; Kejiang Lei; Huijie Wei; Minbo Zhang; Haoran Wang; Jin Xu (Fuel, 2025)

Oxygen-containing functional groups of biochars enhancing the oxygen release of CaO2 and the generation of free radicals - Qiang Hu; Junheng Zhang; Yadi Pan; Kuan Ding; Chaoyang Xu; Jinyu Hou; Wuxing Liu; Chanchana Thanachayanont; Thipjak Na Lampang; Meiling Chen; Shu Zhang (Process Safety and Environmental Protection, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Ferrihydrite sulfidation transformation and coupled As(V) and Cd(II) mobilization under anoxic conditions - Xiaoming Zhao; Xu Ma; Yuyin Ma; Zidan Yuan; Shaofeng Wang; Yuanming Pan; Meiling Shi; Jinru Lin (Journal of Hazardous Materials, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Microbial mechanism and CO2 emission from coastal saline soil: The role of corn stover and nutrient additions - Qiao Xu; Ling Zhang; Yingdong Zhao; Caixian Tang; Yinjuan Li; Meiling Xu; Xiaozhi Wang (Environmental Research, 2025)

Divergent mitigation mechanisms of soil antibiotic resistance genes by biochar from different agricultural wastes - Yu Yao; Peiyang Yang; Bin Wang; Qiao Xu; Fanhao Song; Yabo Wang; Yingdong Zhao; Lei Guo; Xiaozhi Wang; Meiling Xu (Environmental Pollution, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Rapid visual detection of glutathione in vegetables and distinguishing multiple sulfur-containing compounds by smartphone-assisted sensor based on calcined PPy@CuNi-ZIF-67 nanozyme with enhanced oxidase-like activity - Linchun Nie; Jiazhi Xia; Jiawei Liao; Na Liu; Meiling Xu; Dejing Meng; Wenjing Liu; Qingxiang Zhou; Chunmao Chen (Food Chemistry, 2025)

Unraveling the trisubstrate-triproduct reaction mechanisms of wine grape VvCYP76F14 to improve wine bouquet - Zhizhong Song; Meiling Tang; Huilin Xiao; Houhua Xu; Matthew Shi; Adeeba Dark; Zhenqiang Xie; Bin Peng (Food Chemistry, 2025)

Sensitive measurement of polycyclic aromatic hydrocarbons based on strong enrichment from magnetic covalent organic framework before high performance liquid chromatography analysis - Guangyu Dong; Liushan Jiang; Linchun Nie; Jiawei Liao; Xiaodie Geng; Wenjing Liu; Dejing Meng; Meiling Xu; Na Liu; Qingxiang Zhou; Chunmao Chen (Journal of Environmental Chemical Engineering, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

A Hypothetical Protein Fragment from Large Yellow Croaker (Larimichthys crocea) Demonstrates Significant Activity Against Both Bacterial and Parasite - Chunmei Yan; Meiling Chen; Hao Xu; Jian Jin; Xiande Liu; Zhiyong Wang; Dongling Zhang (Fishes, 2025)
Antimicrobial peptides (AMPs) are biocompatible and biodegradable, making them an attractive alternative to traditional antimicrobial agents and chemical preservatives. Here, a novel α-helix amphiphilic anionic AMP Lc149 was screened from a large yellow croaker (Larimichthys crocea) using a Bacillus subtilis expression system. Lc149 is a hypothesized protein fragment not annotated in the genome of a large yellow croaker. Both extracellular protein and recombinant Lc149 (rLc149) exhibited significant killing effects against Gram-negative Escherichia coli and Vibrio harveyi. Scanning and transmission electron microscopy revealed that rLc149 had the ability to disrupt bacterial cell membranes, causing irregular cell morphology, severe cell membrane damage, cytoplasm agglutination, and intracellular content leakage. Confocal laser scanning microscopy and flow cytometry further confirmed bacterial cell destruction and mortality rates of over 80%. Gel retardation assays and SDS-PAGE electrophoresis showed that rLc149 was unable to bind to bacterial DNA, but did reduce bacterial protein contents. Additionally, rLc149 maintained antibacterial activity against E. coli and V. harveyi upon exposure to temperatures of 25–100 °C, UV radiation time of 0–60 min, pH levels of 3–12, and different proteases. Biosafety assays revealed low hemolytic toxicity to erythrocytes of large yellow croaker, rabbit, and shrimp, and low cytotoxicity to large yellow croaker kidney cells and HEK 293T cells. More deeply, rLc149 also possessed significant killing activity against parasites. Therefore, rLc149 can be considered an antibacterial and antiparasitic drug in fisheries.

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Investigation of the effects of polyethylene microplastics at environmentally relevant concentrations on the plant-soil-microbiota system: A two-year field trial - Meiling Xu; Wenqian Ma; Yu Yao; Qiao Xu; Wenchao Du; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Science of The Total Environment, 2024)

Investigating CO₂ sequestration via enhanced rock weathering: Effects of temperature and citric acid on dolomite and basalt - Qiao Xu; Feifan Zhang; Fanhao Song; Hongyan Guo; Xiaozhi Wang; Fenfen Bi; Meiling Xu (Journal of Cleaner Production, 2024)

Bacteria contribute more than fungi to SOC decomposition in a paddy field under long-term free-air CO2 enrichment - Meiling Xu; Feifan Zhang; Ling Zhang; Hongze Zhang; Caixian Tang; Xiaozhi Wang; Jing Ma; Qiao Xu (European Journal of Soil Biology, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

Development of multi-cross-linking, rapid curing, and easy cleaning, edible hydrogels for meat preservation - Yuxin Cheng; Jiaxin Xu; Rongfan Zhang; Jianguo Lin; Meiling Zhou; Xianmin Qin; Keshan Wang; Ying Zhou; Qiujin Zhu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Three nona-2,7-dienoic acid derivatives from saltern derived Micromonospora sp. FXY415 - Meiling Wang; Zhonghui Zheng; Zhiyu Hu; Binbin Fan; Jiexi Liu; Qingyan Xu (Natural Product Research, 2024)

Elevated CO2 exacerbates the risk of methylmercury exposure in consuming aquatic products: Evidence from a complex paddy wetland ecosystem - Danni Wu; Lei Chen; Xueying Zong; Fan Jiang; Xiaojie Wang; Meiling Xu; Fuxun Ai; Wenchao Du; Ying Yin; Hongyan Guo (Environmental Pollution, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Calcium isotopic compositions of eclogite melts and negligible modification during reaction with lithospheric mantle - Zongqi Zou; Zaicong Wang; Xiao-Jun Wang; Yi-Gang Xu; Li-Hui Chen; Meiling Wang; Lanping Feng; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Dual responsive cellulose-based fluorescent material fabricated in a CO2 switchable solvent for multifunctional applications - Yiting Xu; Xiaobo Yu; Meiling Chen; Yi Sun; Wei Zhang; Yajin Fang; Lanyun Fang; Haining Na; Fei Liu; Jin Zhu (Chemical Engineering Journal, 2023)

Investigating the effects of organic amendments on soil microbial composition and its linkage to soil organic carbon: A global meta-analysis - Jiwen Cui; Binggeng Yang; Meiling Zhang; Dali Song; Xinpeng Xu; Chao Ai; Guoqing Liang; Wei Zhou (Science of The Total Environment, 2023)

Designing a cercosporin-bioinspired bifunctional algicide with flocculation and photocatalysis for efficiently controlling harmful cyanobacterial blooms - Zhenbo Yuan; Meiling Liu; Zengping Su; Huibin Xu; Changmei Liu; Liushen Lu; Lingling Wang; Xiaonan Zhu; Yan Zhang; Yijian Rao (Journal of Hazardous Materials, 2023)

Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Kui Ding; Pengji Zhuo; Meiling Ge; Xiaomei Liao; Jing Mo; Shilin Liu; Qinzeng Xu; Xuelei Zhang (Frontiers in Marine Science, 2023)
Introduction Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers. Methods Using ltra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Triple-TOF-MS), we investigated the metabolic impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on the body wall of Apostichopus japonicus . etabolite changes and metabolic pathway alterations were assessed in response to three distinct concentrations of BDE-47: 0.1 µg/L, 1.0 µg/L, and 10.0 µg/L. REsults Exposure to BDE-47 led to notable alterations in the metabolic profiles of the body wall. A total of 95~102 metabolites in the 0.1 ~ 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. These metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. Discussion The findings of our study shed light on the potential health risks that polybrominated diphenyl ethers present to sea cucumbers. This underscores the imperative for both researchers and policymakers to delve deeper into further investigations and studies. These results indicate the necessity for enhanced monitoring and management practices within the sea cucumber aquaculture industry to mitigate the impact of these persistent organic pollutants and protect the health and safety of this valuable resource.

Fine genetic mapping confers a major gene controlling leaf shape variation in watermelon - Ming Xu; Meiling Gao; Sikandar Amanullah; Yu Guo; Xiuping Bao; Yaru Duan; Xiujie Liu; Jixiu Liu; Yue Gao; Feishi Luan (Euphytica, 2023)

Insight into the molecular mechanism of phosphine toxicity provided by functional analysis of cytochrome b5 fatty acid desaturase and dihydrolipoamide dehydrogenase in the red flour beetle, Tribolium castaneum - Xu Shen; Meiling Che; Honglei Xu; Xinbo Zhuang; Erhu Chen; Peian Tang; Kangxu Wang (Pesticide Biochemistry and Physiology, 2023)

Efficacy and safety of IL-23 inhibitors in the treatment of psoriatic arthritis: a meta-analysis based on randomized controlled trials - Xiaojing Huang; Haojie Shentu; Yujing He; Haijia Lai; Chen Xu; Meiling Chen; Haowei Zhu (Immunologic Research, 2023)
In recent years, the use of interleukin (IL) 23 inhibitors in the treatment of psoriatic arthritis (PsA) has been the subject of much research. By specifically binding to the p19 subunit of IL-23, IL-23 inhibitors block downstream signaling pathways and inhibit inflammatory responses. The objective of this study was to assess the clinical efficacy and safety of IL-23 inhibitors in the treatment of PsA. PubMed, Web of Science, Cochrane Library, and EMBASE databases were searched from the time of conception to June 2022 for randomized controlled trials (RCTs) investigating the use of IL-23 in PsA therapy. The main outcome of interest was the American College of Rheumatology 20 (ACR20) response rate at week 24. We included six RCTs (3 studies on guselkumab, 2 on risankizumab, and 1 on tildrakizumab) with a total of 2971 PsA patients in our meta-analysis. We found that the IL-23 inhibitor group showed a significantly higher ACR20 response rate compared to the placebo group (relative risk = 1.74, 95% confidence interval: 1.57–1.92; P < 0.001; I 2 = 40%). There was no statistical difference in the risk of adverse events ( P = 0.07) and serious adverse events ( P = 0.20) between the IL-23 inhibitor and placebo groups. Notably, the rate of elevated transaminases in the IL-23 inhibitor group was higher than the placebo group (relative risk = 1.69; 95%CI 1.29–2.23; P < 0.001; I 2 = 24%). In the treatment of PsA, IL-23 inhibitors significantly outperform placebo intervention while maintaining a favorable safety profile.

Memristive competitive hopfield neural network for image segmentation application - Cong Xu; Meiling Liao; Chunhua Wang; Jingru Sun; Hairong Lin (Cognitive Neurodynamics, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

Tet Enzyme-Mediated Response in Environmental Stress and Stress-Related Psychiatric Diseases - Meiling Xia; Rui Yan; Myoung-Hwan Kim; Xingshun Xu (Molecular Neurobiology, 2023)

Elevated CO2 exacerbates effects of TiO2 nanoparticles on rice (Oryza sativa L.) leaf transcriptome and soil bacteria - Wenqian Ma; Wenchao Du; Kaihua Gu; Meiling Xu; Ying Yin; Yuanyuan Sun; Jichun Wu; Jianguo Zhu; Hongyan Guo (Science of The Total Environment, 2023)

Diesel removal and recovery from heavily diesel-contaminated soil based on three-liquid-phase equilibria of diesel + 2-butyloxyethanol + water - Zhijie Shang; Pan Xu; Zhenyu Ke; Meiling Yao; Xinxue Li (Journal of Hazardous Materials, 2023)

Elevated CO2 aggravated polystyrene microplastics effects on the rice-soil system under field conditions - Meiling Xu; Qiao Xu; Guobing Wang; Wenchao Du; Jianguo Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Environmental Pollution, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

Molecular mapping of candidate gene regulating fruit stripe trait in watermelon - Xiaoxue Liang; Meiling Gao; Sikandar Amanullah; Yu Guo; Hongguo Xu; Xiaosong Liu; Xiujie Liu; Jixiu Liu; Yue Gao; Chengzhi Yuan; Xuezheng Wang; Feishi Luan (Euphytica, 2022)

Morphological and endogenous phytohormone changes during long-term embryogenic cultures in Korean pine - Yan Liang; Xin Xu; Hailong Shen; Meiling Gao; Yan Zhao; Xue Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Effects of Microplastics on Higher Plants: A Review - Jia Li; Songguo Yu; Yufei Yu; Meiling Xu (Bulletin of Environmental Contamination and Toxicology, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Integrated Assessment of Cd-contaminated Paddy Soil with Application of Combined Ameliorants: A Three-Year Field Study - Guobing Wang; Wenchao Du; Meiling Xu; Fuxun Ai; Ying Yin; Hongyan Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Liver kinase B1 (LKB1) reduced inflammation and oxidative stress by regulating the AMPK/NLRP3 signaling pathway in LPS-induced lung injury - Yifeng Yue; Liwu Zong; Yongmin Chen; Nianhai Feng; Junxia Tang; Hongyu Xu; Meiling Zhao (Molecular & Cellular Toxicology, 2021)

A new parametric segmentation method based on sandy mudstone SEM images - Meiling Zhou; Jianlin Li; Weijie Xu; Feng Xu; Eleyas Assefa; Huafeng Deng (Arabian Journal of Geosciences, 2021)

Identification and genomic characterization of emerging CRESS DNA viruses in thoroughbred horses in China - Panpan Tong; Meiling Ren; Xinlong Xu; Xiaozhen Song; Lei Zhang; Ling Kuang; Jinxin Xie (Virus Genes, 2021)

Dextran sulfate–modified pH-sensitive layered double hydroxide nanocomposites for treatment of rheumatoid arthritis - Xiahui Wang; Bowen Yang; Xiaowen Xu; Meiling Su; Mingrong Xi; Zongning Yin (Drug Delivery and Translational Research, 2021)

Divergence in response of japonica and hybrid rice to titanium dioxide nanoparticles - Meiling Xu; Lu Mao; Wenchao Du; Hongyan Guo; Ying Yin (Journal of Soils and Sediments, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

The Effect of Composting on the Multiple Heavy Metals in the River Sediment Investigated by Multivariate Analysis - Yaoning Chen; Yanrong Chen; Yuanping Li; Yihuan Liu; Daoli Zhang; Yanxin Wu; Hui Li; Fangting Xu; Meiling Li (Water, Air, & Soil Pollution, 2021)

Functional wastepaper-montmorillonite composite aerogel for Cd2+ adsorption - Yaoning Chen; Yihuan Liu; Yuanping Li; Li Zhao; Yanrong Chen; Hui Li; Yuqing Liu; Linshenzhang Li; Fangting Xu; Meiling Li (Environmental Science and Pollution Research, 2020)

Conversion of cotton textile wastes into porous carbons by chemical activation with ZnCl2, H3PO4, and FeCl3 - Meiling Xia; Xiaohou Shao; Zhenhua Sun; Zhihua Xu (Environmental Science and Pollution Research, 2020)

Genome-wide identification of the pectate lyase-like (PLL) gene family and functional analysis of two PLL genes in rice - Yinzhen Zheng; Junjie Yan; Shuzhen Wang; Meiling Xu; Keke Huang; Guanglong Chen; Yi Ding (Molecular Genetics and Genomics, 2018)

Gut Microbiota and its Modulation for Healthy Farming of Pacific White Shrimp Litopenaeus vannamei - Erchao Li; Chang Xu; Xiaodan Wang; Shifeng Wang; Qun Zhao; Meiling Zhang; Jian G. Qin; Liqiao Chen (Reviews in Fisheries Science & Aquaculture, 2018)

Important interaction of chemicals, microbial biomass and dissolved substrates in the diel hysteresis loop of soil heterotrophic respiration - Qing Wang; Nianpeng He; Yuan Liu; Meiling Li; Li Xu; Xuhui Zhou (Plant and Soil, 2018)

Latitudinal patterns and influencing factors of soil humic carbon fractions from tropical to temperate forests - Li Xu; Chunyan Wang; Jianxing Zhu; Yang Gao; Meiling Li; Yuliang Lv; Guirui Yu; Nianpeng He (Journal of Geographical Sciences, 2018)

Experimental wave attenuation study over flexible plants on a submerged slope - Zegao Yin; Xiaoyu Yang; Yuanzhao Xu; Meiling Ding; Haixiang Lu (Journal of Ocean University of China, 2017)

Comparative genomic analysis of three white spot syndrome virus isolates of different virulence - Fang Li; Meiling Gao; Limei Xu; Feng Yang (Virus Genes, 2017)

Accumulation of intact sulfur mustard in adipose tissue and toxicokinetics by chemical conversion and isotope-dilution liquid chromatography–tandem mass spectrometry - Bin Xu; Cheng Zong; Yajiao Zhang; Tianhong Zhang; Xiaoying Wang; Meiling Qi; Jianfeng Wu; Lei Guo; Peng Wang; Jia Chen; Qin Liu; Hua Xu; et al. (Archives of Toxicology, 2017)

A comparative analysis of the evolution, expression, and cis-regulatory element of polygalacturonase genes in grasses and dicots - Ying Liang; Youjian Yu; Jinlong Cui; Meiling Lyu; Liai Xu; Jiashu Cao (Functional & Integrative Genomics, 2016)

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis - Ying Liang; Youjian Yu; Xiuping Shen; Heng Dong; Meiling Lyu; Liai Xu; Zhiming Ma; Tingting Liu; Jiashu Cao (Plant Molecular Biology, 2015)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Analysis of ΔpH and the xanthophyll cycle in NPQ of the Antarctic sea ice alga Chlamydomonas sp. ICE-L - Shanli Mou; Xiaowen Zhang; Naihao Ye; Jinlai Miao; Shaona Cao; Dong Xu; Xiao Fan; Meiling An (Extremophiles, 2013)

Genome-wide identification, classification, and expression analysis of CDPK and its closely related gene families in poplar (Populus trichocarpa) - Ran Zuo; Ruibo Hu; Guohua Chai; Meiling Xu; Guang Qi; Yingzhen Kong; Gongke Zhou (Molecular Biology Reports, 2013)

Patterns of asynchrony for phytoplankton fluctuations from reservoir mainstream to a tributary bay in a giant dendritic reservoir (Three Gorges Reservoir, China) - Yaoyang Xu; Qinghua Cai; Meiling Shao; Xinqin Han (Aquatic Sciences, 2012)

Temporal Asynchrony of Trophic Status Between Mainstream and Tributary Bay Within a Giant Dendritic Reservoir: The Role of Local-Scale Regulators - Yaoyang Xu; Meiling Shao; Xinqin Han; Qinghua Cai (Water, Air, & Soil Pollution, 2011)

Factors regulating trophic status in a large subtropical reservoir, China - Yaoyang Xu; Qinghua Cai; Xinqin Han; Meiling Shao; Ruiqiu Liu (Environmental Monitoring and Assessment, 2010)